Origins and characteristics of urban wet weather pollution in combined sewer systems: The experimental urban catchment ‘‘Le Marais’’ in Paris - Gromaire-Mertz, M.C.; Chebbo, G.; Saad, M. (Water Science and Technology, 1998)
An experimental urban catchment has been created in the centre of Paris, in order to obtain a description of the pollution of urban wet weather flows at different levels of the combined sewer system, and to estimate the contribution of runoff, waste water and sewer sediments to this pollution. Twenty-two rainfall events were studied from May to October 1996. Dry weather flow was monitored for one week. Roof, street and yard runoff, total flow at the catchment outlet and waste water were analysed for SS, VSS, COD and BOD5, on both total and dissolved fraction. Results show an evolution in the characteristics of wet weather flow from up to downstream: concentrations increase from the catchment entry to the outlet, as well as the proportion of particle-bound pollutants and the part of organic matter. A first evaluation of the different sources of pollution establishes that a major part of wet weather flow pollution originates from inside the combined sewer, probably through erosion of sewer sediments. (C) 1998 IAWQ, Published by Elsevier Science Ltd.